View of Flora Fountain looking towards Churchgate railway station - Ghosh, Ayan (Jio Institute, 2023)
View of Flora Fountain looking towards Churchgate railway station with double turret of Central Telegraph Office and the revolving restaurant of Ambassador Hotel visible in the backdrop. Flora Fountain was installed in 1869 at the intersection of Dadabhai Naoroji Road, Mahatma Gandhi Road and Veer Nariman Road.